Sengketa Lahan Pembangunan Hunian Tetap Kota Palu - Syugiarto Syugiarto; Khairul Umam Karim; Handi Wahyu Kusnadi U. Tadja Lembah (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2021)
This study aims to determine the level of conflict escalation caused by land disputes for permanent residential development in Palu City, and also to find out what methods the Palu City government can use in overcoming this problem. The data collection method used in this research is literature study. The theory used to see the level of conflict escalation is to use the dynamics of conflict stages, which divides these stages into Latent Conflict (Conditions), Perceived Conflict (Cognition), Felt Conflict (Affect), Manifest Conflict (Behavior) and Conflict Aftermath (Condition). Meanwhile, to find out the methods that can be used by the Palu City government in overcoming this conflict, namely by using the Thomas-Kilmann Conflict Mode Instrument. The results of this study indicate that the conflict that occurs in land disputes for permanent residential development (huntap) III is not only a vertical conflict between the government and the community, but the horizontal conflict between the Palu City government and the Palu City DPRD is also seen in it. For this reason, the method that can be used in solving these problems is by conducting collaborative negotiations so that neither party is harmed, and also to show that the Palu City government pays attention to the aspirations of the community.